Growth and Convergence in a Two-Region Model The Hypothetical Case of Korean Unification - Funke, Michael (International Monetary Fund, 2002)
The paper discusses the impact and implications of Korean unification by setting up a two-region endogenous growth model. The numerical solutions are based on the formal analytical model, and have been calibrated so that they reflect the observed features of the North and South Korean economies. The numerical solutions provide evidence about the speed of convergence and the large amount of interregional transfers that are required to make the North Korean economy economically viable